Penerapan Perilaku Hidup Bersih dan Sehat dalam Menanamkan Nilai Karakter Siswa - Millaty Azka Makhsyari; Diana Endah Handayani; Singgih Adhi Prasetyo (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
The purpose of this research is to know the application of clean and healthy life behavior in inculcating the character value of in class IV SDN 1 Kunjeng, Gubug Subdistrict, Grobogan Regency, Central Java Province. The method used in this research is qualitative descriptive research. Data collected by using interviews, observations, questionnaires and documents. The results showed implementation of clean and healthy life behavior in SDN 1 Kunjeng. While the values that exist in the application of clean and healthy life behavior are: 1) religious, 2) honest, 3) discipline, 4) creative, 5) independent, 6) friendly/communication, 7) environmental care, 8) social care, and 9) responsibility